Enrichment activities in elementary science for grade five fast learners - Lacuesta, Loreto Gascon 1924- (1967)
The aims of this study were: 1) to determine what enrichment activities can be included in the elementary science curriculum for grade five fast learners, and 2) to evaluate these activities in terms of concept and skill development. The proposed curriculum guide of the Bureau of Public Schools for Grade Five Elementary Science was used to determine the scope of its content and the science concepts and skills to be developed. The researcher found out that enrichment in science for grade five embraces the three science areas in the curriculum: living things, matter, energy and motion, and the earth today. Emphasis was placed on the learning of concepts through the process approach.